2020
DOI: 10.1101/2020.03.05.979146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional delineation of tissue-resident CD8+T cell heterogeneity during infection and cancer

Abstract: Unremitting defense against diverse pathogens and malignancies requires a dynamic and durable immune response. Tissue-resident memory CD8 + T cells (TRM) afford robust protection against infection and cancer progression through continuous surveillance of non-lymphoid tissues. Here, we provide insight into how TRM confer potent and persistent immunity through partitioning of distinct cellular subsets differing in longevity, effector function, and multipotency. Antigen-specific CD8 + T cells localized to the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
(117 reference statements)
3
10
0
Order By: Relevance
“…In addition to T EM cell subsets and consistent with our data, heterogeneity within T RM cells exists (Kumar et al, 2017(Kumar et al, , 2018Milner et al, 2020). The latter is of interest, because these resident CD8 + T cells contribute significantly to local immunity (Gebhardt et al, 2009;Masopust et al, 2010;Steinert et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…In addition to T EM cell subsets and consistent with our data, heterogeneity within T RM cells exists (Kumar et al, 2017(Kumar et al, , 2018Milner et al, 2020). The latter is of interest, because these resident CD8 + T cells contribute significantly to local immunity (Gebhardt et al, 2009;Masopust et al, 2010;Steinert et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Another single-cell sequencing results showed that Trm cells could be divided into three subsets: Hobitenriched CD103 hi PD-1 lo Trm, Granzyme K-enriched CD103 lo PD-1 hi Trm, and CD103 hi PD-1 hi CTLA hi LAG3 hi TIGIT hi Trm, while the last subset is considered as exhaustion-related subtype (79). Milne et al also identified subsets of memory T cells with resident gene expression characteristic of progenitor exhaustion T (Tpex) cell (Id3 hi Blimp1 lo ) and terminal exhaustion (80), and this study indicates that there exists a complete developmental pathway to exhaustion in Trm. In general, Trm cells may keep their function with the expression of immune checkpoints, but they still can convert into exhausted T cells.…”
Section: Anti-tumor Effect Of Tissue-resident Memory T Cells and T Ce...supporting
confidence: 53%
“…First, what molecular mechanisms confer supe-rior fitness upon antigen-specific Trm cells, compared to bystander Trm cells, particularly in situations when active TGFb is limiting? Antigen-specific and bystander Trm cells exhibited similar transcriptomes, raising the possibility that epigenetic disparities or heterogeneity within these Trm cell populations, as has recently been observed (Kurd et al, 2020;Milner et al, 2020), might account for these differences. Second, precisely how TGFb controls the persistence of Trm cells remains incompletely understood.…”
mentioning
confidence: 85%